Gene Expression Response of Salmonella enterica Serotype Enteritidis Phage Type 8 to Subinhibitory Concentrations of the Plant-Derived Compounds Trans-Cinnamaldehyde and Eugenol - Kollanoor Johny, Anup; Frye, Jonathan G.; Donoghue, Annie; Donoghue, Dan J.; Porwollik, Steffen; McClelland, Michael; Venkitanarayanan, Kumar (Frontiers in Microbiology, 2017)
Salmonella Enteritidis phage type 8 (PT8) is a major poultry-associated Salmonella strain implicated in foodborne outbreaks in the United States. We previously reported that two plant-derived compounds generally recognized as safe (GRAS), trans-cinnamaldehyde (TC) and eugenol (EG), significantly reduced S. Enteritidis colonization in broiler and layer chickens. To elucidate potential PT8 genes affected by TC and EG during colonization, a whole-genome microarray analysis of the bacterium treated with TC and EG was conducted. S. Enteritidis PT8 was grown in Luria-Bertani broth at 37oC to an OD600 of ~0.5. Subinhibitory concentrations (SICs; concentration that does not inhibit bacterial growth) of TC (0.01%; 0.75mM) or EG (0.04%; 2.46mM) were then added to the culture. S. Enteritidis PT8 RNA was extracted before and 30 min after TC or EG addition. Labeled cDNA from three replicate experiments was subsequently hybridized to a microarray of over 99% of S. Enteritidis PT4 genes, and the hybridization signals were quantified. The plant-derived compounds down-regulated (P<0.005) expression of S. Enteritidis PT8 genes involved in flagellar motility, regulation of the Salmonella Pathogenicity Island 1, and invasion of intestinal epithelial cells. TC and EG also suppressed transcription of genes encoding multiple transport systems and outer membrane proteins. Moreover, several metabolic and biosynthetic pathways in the pathogen were down-regulated during exposure to the plant-derived compounds. Both TC and EG stimulated the transcription of heat shock genes, such as dnaK, dnaJ, ibpB and ibpA in S. Enteritidis PT8 (P<0.005). The results obtained from microarray were validated using a quantitative real-time PCR. The plant - derived compounds TC and EG exert antimicrobial effects on S. Enteritidis PT8 by affecting multiple genes, including those associated with virulence, colonization, cell membrane composition, and transport systems.